Plasma Nanotechnology for Controlling Chemical and Physical Properties of Organosilicon Nanocoatings. (September 2020) - Branecky, Martin; Aboualigaledari, Naghmeh; Cech, Vladimir
Graphical abstract: Highlights: Plasma nanotechnology as a technique for synthesis of well-defined materials. Controlled dissociation and consumption of precursor molecules. From polymer-like to tough materials due to increased network crosslinking. Correlation between physical and chemical properties of coatings. Construction of more complex nanostructures with high reproducibility. Abstract: Organosilicon nanocoatings are key materials that are part of many mechanical, optical, electronic, and medical devices and are essential to optimize the surface properties of any type of material with respect to the application. Because of such a wide range of applications, the chemical and physical properties of coatings need to be controlled within wide ranges, which is difficult to achieve by a single coating process. Plasma nanotechnology, based on controlled dissociation and consumption of the precursor molecule, is presented as the appropriate technique for the synthesis of well-defined materials with controllable properties. Tetravinylsilane is selected as the precursor molecule to demonstrate the range of coating properties achieved, from a polymer-like to a tough material with a gradually varying organic-inorganic character. The removal of hydrogen from the carbon-silicon network of the coating is responsible for its increased crosslinking that controls both the mechanical and optical properties of the coating. A more crosslinked coating contains a lower concentration of vinyl groups but a higher sp 2 bond fraction, resulting in a drop of the band gap from 2.6 to 1.0 eV. It is shown that plasma nanotechnology allows the construction of more complex nanostructures with high reproducibility.